AKTIVITAS ANTIBAKTERI MINUMAN FUNGSIONAL SARI TEMPE KEDELAI HITAM DENGAN PENAMBAHAN EKSTRAK JAHE (STUDY OF ANTIBACTERIAL ACTIVITY FUNCTIONAL DRINKS OF BLACK SOYBEAN TEMPE WITH ADDITION GINGER EXTRACT) - Nurhidajah Nurhidajah (Universitas Muhammadiyah Semarang, 2010)
Nutrition in Tempe can be useful for metabolic reactions, also contains a natural antibiotic that can inhibit the emergence of various diseases, such as antibacterial components which are very beneficial to health. Beverage products form tempe which The addition of ginger extract on the functional beverage black soybean tempe. This study consists of 2 stages. Phase I is introductory, covering the manufacture of black soybean tempe (2 times the boiling), followed by analysis of water and protein content, then phase 2 is a functional beverage processing optimization with ginger extract additional variation were 0 %, 1%, 2%, 3% and 4%, in treatment that is by non-instant and instant. The design of the study in phase 2 is 5x2 factorial experiment using a Completely Randomized Design. The first factor is the addition of ginger extract with 5 variations, and the second factor of 2 variations of processing, so there were 10 treatment combinations. The results showed black soybean tempe has a water content of 61.81%, protein 20.36%, fat 2.9% and 0.97% ash. Organoleptic assessment showed non instant processing has a flavor that is higher than processed an instant. Protein consentration of black soybean tempe functional beverage with the highest non-instant processing with the addition of ginger extract 2%. Drink black soybean tempe has a relatively weak antibacterial activity (<5 mm), and there is the influence of treatment with antibacterial activity in soybean tempe drink black. suggested further research to otimasi black soybean tempe beverage processing and processing of instant non-instantaneous with the addition of ginger extract at least 4%. Key words: black soybean, functional drinks, antibacterial activity